Kongsfjorden Ecosystem - a Nitrogen Sink during the Arctic Summer. - Duarte, Pedro; Fransson, Agneta; Chierici, Melissa; Gabrielsen, Geir W.; Hop, Haakon; Assmy, Philipp; Tripathy, Sarat Chandra; Azzaro, Maurizio; Convey, Peter; Alexander, Andreas; Langone, Leonardo; Aguilar Vega, Ximena; et al. (My University, 2023)
Kongsfjorden nitrogen budget is dominated by exchanges of nitrate with the sea. The fjord is a nitrogen and carbon sink during summer. The C:N molar ratio of the Source-Sink term is 7.3, which is close to the expected Redfield ratio (6.6). Negative nutrient and carbon sink indicate autotrophic metabolism.
Keywords: Agua - Contenido de nitrógeno; Ecología de fiordos; Carbono; Arctic; Nitrogen budget